Analysis of Opportunity Coston Land Utilization of Soybean and Corn Farming in Watubangga Sub-district, District of Kolaka - Kartomo Kartomo (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2017)
This study aimed to analyze the utilization of agricultural land and income difference between soybean (Glycine max L Merril) farming and corn (Zea mays L)farming in Watubangga sub-District, District of Kolaka. Data were collected by survey and interview and analyzed using an income approach and mean difference test for 65 samples of heads of households (KK).The results of data analysis showed that the opportunity cost of land utilization was Rp 5.481.651/ Ha which caused by choosing soybean farming. The result also showed a significant difference in land utilized for soybean and corn farming. The Result of study suggested the farmers cultivate corn.